With the “schiavitù della schiena”: Rovani and the Construction of a Language for the Novel (Altre Modernità, 2025)
This paper aims at investigating the genesis of the language employed by Giuseppe Rovani in his novel Cento anni (1859), starting from the very first literary apprenticeship, characterized by a frank Tuscan matrix, represented by his Eleonora da Toledo (1841). Through the comparison with contemporary narrative texts and lexicographic tools, I will try to outline the parable of bookish archaisms and idiomatic expression, both Lumbard and Tuscan, and thus arrive at a first hypothesis of description and interpretation of the linguistic-stylistic configuration of the most significant work written by the Milanese author).
Keywords: Giuseppe Rovani; Italian linguistics; Stylistics of literary texts; Cento anni; Historical novel